Quantitative autofluorescence is increased in clinically unaffected fellow eyes from patients with posterior uveitis - Finger, Robert P.; Jungblut, Julie; Just, Marie D.; Terheyden, Jan H.; Holz, Frank G.; Liegl, Raffael; Ach, Thomas; Wintergerst, Maximilian W. M. (Scientific reports, 2025)
The purpose of this prospective case-control study is to investigate differences in quantitative autofluorescence (qAF) in clinically affected and unaffected eyes of patients with inactive posterior uveitis compared to healthy, age-matched controls. Patients with posterior uveitis and healthy controls were imaged using fundus autofluorescence (488 nm excitation; Spectralis HRA + OCT; Heidelberg Engineering) to measure qAF values using the proprietary HEYEX software. Mean background qAF (excluding vessels and retinal lesions) across all segments (as previously defined by Delori et al.) and in the segment with the highest mean qAF value were compared between affected and unaffected eyes from patients with posterior uveitis, and healthy age-matched control eyes using the Kruskal-Wallis-test. A total of 83 eyes from 83 patients were included: 33 affected eyes (33 patients with uni-/bilateral posterior uveitis), 21 clinically unaffected eyes (21 patients with unilateral posterior uveitis), and 29 healthy, age-matched control eyes (29 patients). Mean qAF values were significantly higher (p-value < 0.0001) in both clinically affected (177.0 ± 83.8 qAF arbitrary units [qAF a.u.]) and unaffected (173.8 ± 56.4 qAF a.u.) eyes compared to healthy, age-matched controls (135.7 ± 41.8 qAF a.u.). Likewise, mean qAF in the segment with the highest mean qAF value was significantly higher (p-value: <0.01) in affected (243.2 ± 103.1 qAF a.u.) and unaffected eyes (227.1 ± 63.4 qAF a.u.) in comparison to controls (168.9 ± 48.5 qAF a.u.). In conclusion, both clinically affected and unaffected eyes from patients with posterior uveitis demonstrated increased fundus autofluorescence. The results of our study could indicate subclinical inflammation in currently inactive and (yet) unaffected eyes of posterior uveitis patients. This could be caused by accumulation of fluorophores or an increased metabolic activity generated by low-grade inflammation. As these changes may precede future inflammation in yet unaffected eyes, additional longitudinal studies including analysis of eyes with active disease are warranted.
Gesehen am 10.07.2025